Effect of povidone iodine contact lens disinfecting solution on orthokeratology lens and lens case contamination and organisms in the microbiome of the conjunctiva. Issue 6 (December 2021) - Cheung, Sin Wan; Boost, Maureen Valerie; Cho, Pauline
Abstract: Purpose: To compare lens cleaning routines using a povidone iodine-based rigid lens disinfecting solution and its effect on conjunctival colonisation, and lens and lens case contamination. Methods: Participants, aged 6–10 years, receiving orthokeratology treatment were randomised to four lens cleaning routines: with and without the use of daily and/or weekly cleaners, which were performed by their parents. Conjunctival colonisation was compared before lens wear and at 1-, 3-, and 6-month after commencement of lens wear. Contamination of lenses and lens cases was investigated at these times. Organisms were identified using MALDI-TOF mass spectrometry. Results: Of the 76 participants who completed the study, conjunctival colonization was present in 24 (32 %) at baseline. Of the remaining 52 participants, 34 consistently yielded no growth. Participants positive at baseline were statistically more likely to be colonized after commencement of lens wear (p = 0.020). Overall, colonization rate was reduced to 15 % (11/72) after 6-month lens wear, which reached significance for initially colonized participants (p < 0.001). Few cultures yielded potential ocular pathogens, with notably no Pseudomonas aeruginosa . Contamination rates of both lenses and lens cases were also low, with few isolations of ocular pathogens. No significant differences were observed between cleaning regimes for conjunctival colonization or contamination of lenses or cases. Conclusions: Disinfection for rigid and ortho-k lens wearers may be effectively achieved with the use of povidone iodine-based solution, apparently regardless of cleaning routine adopted in the current study. The absence of pathogens in the conjunctiva, lenses, and lens cases in the great majority of samples indicates that it can improve the safety of overnight lens wear.